(untitled) (Medical Forum Monthly, 2024)
Objective: The aim and objective of this study is to assess the relationship between obesity and severity of Cholecystitis. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted in the Punjab Employees Social Security Hospital Rawalpindi &AzmatRasheed Hospital Rawalpindi from 1st January 2015 to 31st Dec 2015. Materials and Methods: 84 patients of symptomatic gall stone disease were included in the study. BMI was calculated & recorded at the time of admission.Patients having BMI > 25kg/m2 were put in category of overweight/Obese & those having BMI < 25kg/m2 were considered to be of normal weight. Results: In males proportion of complicated acute cholecystitis was significantly higher in non-obese patients and was around (21%) as compared to obese (7%) with significant statistical difference. On the other hand no significant statistical difference was found between female non-obese & obese patients. Conclusion: Contrary to common belief, complication rate in obese males is less as compared to males of normal weight. While in females, no such difference is noted in complication rate of gall stone disease between obese and non-obese females.